Diverse plant promoting bacterial species differentially improve tomato plant fitness under water stress - Zampieri, Elisa; Franchi, Elisabetta; Giovannini, Luca; Brescia, Francesca; Sillo, Fabiano; Fusini, Danilo; Pietrini, Ilaria; Centritto, Mauro; Balestrini, Raffaella (Frontiers in Plant Science, 2023)
Introduction Food crops are increasingly susceptible to the challenging impacts of climate change, encompassing both abiotic and biotic stresses, that cause yield losses. Root-associated microorganisms, including plant growth-promoting bacteria (PGPB), can improve plant growth as well as plant tolerance to environmental stresses. The aims of this work were to characterize bacteria isolated from soil and roots of tomato plants grown in open field. Methods Biochemical and molecular analyses were used to evaluate the PGP potential of the considered strains on tomato plants in controlled conditions, also assessing their effects under a water deficit condition. The isolated strains were classified by 16S gene sequencing and exhibited typical features of PGPB, such as the release of siderophores, the production of proteases, and phosphorous solubilization. Inoculating tomato plants with eleven selected strains led to the identification of potentially interesting strains that increased shoot height and dry weight. Three strains were then selected for the experiment under water deficit in controlled conditions. The tomato plants were monitored from biometric and physiological point of view, and the effect of inoculation at molecular level was verified with a targeted RT-qPCR based approach on genes that play a role under water deficit condition. Results Results revealed the PGP potential of different bacterial isolates in tomato plants, both in well-watered and stressed conditions. The used integrated approach allowed to obtain a broader picture of the plant status, from biometric, eco-physiological and molecular point of view. Gene expression analysis showed a different regulation of genes involved in pathways related to abscisic acid, osmoprotectant compounds and heat shock proteins, depending on the treatments. Discussion Overall, results showed significant changes in tomato plants due to the bacterial inoculation, also under water deficit, that hold promise for future field applications of these bacterial strains, suggesting that a synergistic and complementary interaction between diverse PGPB is an important point to be considered for their exploitation.